Comparison between effects of different doses of Melissa officinalis and atorvastatin on the activity of liver enzymes in hypercholesterolemia rats - Saeed Changizi Ashtiyani; Ali Zarei; Soheila Taheri; Fateme Rasekh (Avicenna Journal of Phytomedicine, 2014)
Objectives: Liver is one of the most sensitive tissues to oxidant damage. Hence, the present study was conducted to compare the effects of Melissa officinalis (MO) extract and Atorvastatin on the activity of liver enzymes in rats. Materials and Methods: In this experimental study, 60 male Wistar rats were selected and allocated to six groups (n=10). The control group received a normal diet, sham group received a fatty diet while other groups received a fatty diet and the alcoholic extract ofMO, at minimum (25 mg/kg), moderate (50 mg/kg), and maximum (75 mg/kg) doses (i.p.). The last group received Atorvastatin (10 mg/kg) through gavage with a fatty diet over a 21-day period. At the end of this 21-day period, blood samples were drawn and the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP), activity of liver enzymes as well as cholesterol in the samples were measured. Results: The obtained results showed that the activity of liver enzymes in the treatment groups receiving MO extract and the group receiving Atorvastatin decreased significantly. MOextract reduced the level of liver enzymes. Conclusion: Therefore, further studies for obtaining a better understanding of the mechanism of effect of MO for treating liver diseases are recommended.